2022
DOI: 10.3389/fcell.2022.931609
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Ureaplasma parvum-infected ectocervical epithelial cells promote feto-maternal interface inflammation but are insufficient to cause preterm delivery

Abstract: This study determined if exosomes from ectocervical epithelial (ECTO) cells infected with Ureaplasma parvum (U. parvum) can carry bacterial antigens and cause inflammation at the feto-maternal interface using two organ-on-chip devices, one representing the vagina-cervix-decidua and another one mimicking the feto-maternal interface, and whether such inflammation can lead to preterm birth (PTB). Exosomes from U. parvum-infected ECTO cells were characterized using cryo-electron microscopy, nanoparticle tracking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Cryo‐EM images showed circular membrane‐bound vesicles (Figure S1). Based on our previous study, U. parvum infection did not significantly change the size and concentrations of exosomes from ECTO cells 26 . We employed NanoLC–MS/MS analysis to perform a proteomic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cryo‐EM images showed circular membrane‐bound vesicles (Figure S1). Based on our previous study, U. parvum infection did not significantly change the size and concentrations of exosomes from ECTO cells 26 . We employed NanoLC–MS/MS analysis to perform a proteomic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study in Rhesus macaques showed the U. parvum only induced mild uterine inflammation without overt chorioamnionitis 24 . Several animal studies also showed that ascending infection with U. parvum was not associated with high preterm birth rates 25,26 . These mechanisms often lead to persistent mild infections with mycoplasmas 27 …”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations